Conflictos del uso de suelo, a través del sistema USDA-LCC mediante SIG como aporte a la sostenibilidad ambiental, microcuenca cañas - Viteri Espinoza, José Paúl (2016)
This aimed research had been evaluating the conflict of land use from their fitness as a contribution to their sustainable use, the scope of which is aimed at all Cañas micro basin, from Calceta city of Bolívar Canton, with the aim of recommend the best use of land in order to raise the productivity of the agricultural sector and food security. For which coverage and current land use in the reeds micro basin through direct observation and analysis of geo referenced satellite image obtained from the virtual platform Earth Explorer the USGS (United States Geological Survey) and SAS was determined Planet version 141212.8406. a map using the ArcGIS software version 10.0 in the quantitative values of coverage and land use and related areas among which are the ground for Forest with 42.14%, Grass with 39.08%, Corps was established that generated water with 7.18%, Arable long cycle with a 6.06%, Arable short cycle with 5.54%, getting through random sampling by crop and altitude sections along with the analysis of the adapted methodology of CLIRSEN and USDA- LCC in the soil land class as Cañas Microcuenca II, III and IV those are presented. For these reasons is presented a guide set for good land use as a contribution to environmental sustainability in microcuencas Cañas